The Relationship between Gadget Usage, Communication Support, and the Risk of Sexually Transmitted Infections among Adolescent Girls in SMA PGRI 1 Bekasi City in 2023 - Dharmawan, Gita Fricilya; Rina A, Tetty; Siregar, Renince (The Health Researcher's Journal, 2024)
Adolescence is a transitional period from childhood to adulthood in Indonesia, especially in West Java, which experiences an increasing number of HIV cases each year. Adolescents contribute to nearly 20% of the total cases, with Kota Bekasi having an adolescent population of 2.48%. The main contributing factors are related to gadget usage, communication, and support. This research aims to further examine the relationship between Gadget Use, Communication, Support, and the Risk of Sexually Transmitted Infections (STIs) among adolescents. The research employs a quantitative method with a Cross-Sectional design. The sample consists of 158 adolescents out of a total of 260. Data collection was conducted over 8 days, with the results indicating a significant relationship between Gadget Use and the Risk of Sexually Transmitted Infections (p-value: 0.005). Similarly, there is a significant relationship between Communication and the Risk of Sexually Transmitted Infections (p-value: 0.009). Support also correlates with the Risk of Sexually Transmitted Infections. Therefore, it is recommended that adolescents receive education regarding the proper use of gadgets, effective communication, and adequate support, with the involvement of parents or guardians.